Jaguar Persecution Without “Cowflict”: Insights From Protected Territories in the Bolivian Amazon - Knox, Jillian; Negrões, Nuno; Marchini, Silvio; Barboza, Kathrin; Guanacoma, Gladys; Balhau, Patricia; Tobler, Mathias W.; Glikman, Jenny A. (Frontiers in Ecology and Evolution, 2019)
Persecution by humans is one of the most pressing threats to jaguars (Panthera onca) throughout the Americas, yet few studies have examined the killing of jaguars outside cattle-ranching communities. Although over one-third of the jaguar’s range is formally protected, relatively little is known about human-jaguar relationships within protected areas and indigenous territories. Protected land within the Bolivian Amazon, considered a stronghold for the jaguar, contains communities who differ economically, legally, and socially from previously-studied human populations living with jaguars. Using in-person structured interviews, we investigated attitudes and norms related to jaguars and jaguar killing, self-reported past killing of jaguars, and demographic variables in two protected areas and an indigenous territory: Integrated Management Area of Santa Rosa del Abuná (Santa Rosa, n=224), Indigenous Territory Tacana II (n=137), and Manuripi National Amazon Wildlife Reserve (MNAWR, n=169). Overall, people disliked (48.9%) or felt neutral (26.8%) toward jaguars. A relatively large number of people reported either being attacked or knowing someone who had been attacked by a jaguar: 15.45% in Santa Rosa, 14.20% in MNAWR, and 30.88% in Tacana II. Many respondents stated to have killed a jaguar, although the proportion differed among study areas: 20.39% of Santa Rosa, 55.47% of Tacana II, and 32.72% of MNAWR. People perceived jaguar persecution as relatively common: 44.9% of Santa Rosa, 90.8% of Tacana II, and 65.8% of MNAWR said their neighbors kill jaguars (i.e. descriptive norm). Also, 75.4% of Santa Rosa, 89.1% of Tacana II, and 69.1% of MNAWR said that some of their family members and neighbors thought jaguar killing was good (i.e. subjective norm). Descriptive and subjective norms positively influenced both attitudes toward killing and past killing of jaguars. This perception of jaguar killing being common and socially-accepted, combined with high rates of past killing and a growing illegal trade of jaguar parts, may create an atmosphere conducive to widespread jaguar persecution in the Bolivian Amazon. We recommend management strategies that focus on preventing jaguar depredation of small domestic animals, lessening the perception of carnivore encounters as dangerous to decrease safety-related fears, and making large carnivore killing socially unacceptable (e.g. through social marketing).